2014
DOI: 10.1093/schbul/sbu170
|View full text |Cite|
|
Sign up to set email alerts
|

Treatments of Negative Symptoms in Schizophrenia: Meta-Analysis of 168 Randomized Placebo-Controlled Trials

Abstract: Although some statistically significant effects on negative symptoms were evident, none reached the threshold for clinically significant improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
365
2
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 565 publications
(382 citation statements)
references
References 49 publications
9
365
2
6
Order By: Relevance
“…These investigators concluded that antidepressants prescribed along with antipsychotics were more effective in treating the negative symptoms of schizophrenia than antipsychotics alone. They reported a small-to-medium effect size (−0.48; p < 0.05), comparable with a later meta-analysis of 26 relevant RCTs by Fusar-Poli et al 57 which yielded similar, respective figures (−0.349; p = 0.001). Nevertheless, a Cochrane review, 58 although agreeing that a combination of antipsychotics and antidepressants may be effective in treating negative symptoms of schizophrenia, considered that the research information available was currently too limited to allow any firm conclusions to be drawn, and that large, pragmatic, well-designed and well-reported long-term trials were justified.…”
Section: Efficacy Of Antidepressant Augmentation For Negative Symptomssupporting
confidence: 79%
“…These investigators concluded that antidepressants prescribed along with antipsychotics were more effective in treating the negative symptoms of schizophrenia than antipsychotics alone. They reported a small-to-medium effect size (−0.48; p < 0.05), comparable with a later meta-analysis of 26 relevant RCTs by Fusar-Poli et al 57 which yielded similar, respective figures (−0.349; p = 0.001). Nevertheless, a Cochrane review, 58 although agreeing that a combination of antipsychotics and antidepressants may be effective in treating negative symptoms of schizophrenia, considered that the research information available was currently too limited to allow any firm conclusions to be drawn, and that large, pragmatic, well-designed and well-reported long-term trials were justified.…”
Section: Efficacy Of Antidepressant Augmentation For Negative Symptomssupporting
confidence: 79%
“…1,9 In spite of the strong negative impact of apathy related symptoms in schizophrenia, 7 treatment studies for this frequent behavioral condition have provided limited evidence of efficiency. 10 One reason for this could be the simplistic conception of apathy, frequently considered as a unitary syndrome. However, there is now evidence that apathy can no longer be considered as a unique construct but rather as a multidimensional and multifaceted psychopathological state comprising cognitive, emotional, behavioral and self-initiation components, with different underlying psychological, biological or environmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent meta-analyses of negative symptom clinical trials revealed most did not even deal with the primary/secondary distinction in discussion and almost none used a study design that would permit an efficacy interpretation. 11 Even as an editor I have little success in bringing strong inference methods into common use. The vast majority of research in our field is not based on an important hypothesis in a theoretical context where negative results force a new conceptualization or where competing hypotheses are separated into valid and nonvalid.…”
Section: W T Carpentermentioning
confidence: 99%